Paradigma Pendidikan Agama Islam Berwawasan Multikultural dalam Menumbuhkan Sikap Toleransi Di SMP Negeri 4 Lamongan - Ahmad Hanif Fahruddin (Universitas Islam Lamongan, 2019)
This research raises the problem of Islamic religious education with a multicultural perspective in fostering tolerance with subjects at SMP Negeri 4 Lamongan. In this study, several things will be examined, namely those related to the paradigm of Islamic religious education with a multicultural perspective and the urgency of Islamic religious education with a multicultural perspective in fostering tolerance. Researchers use qualitative methods and descriptive approaches. The results of the research succeeded in finding, among other things: the paradigm of Islamic religious education with a multicultural perspective obtained through a cognitive approach, experience and habituation approach, and through exemplary methods. Besides, Islamic education with a multicultural perspective also fosters a harmonious life attitude, respect, and respect, fosters a tolerant attitude and can create a learning climate and academic atmosphere in a conducive learning process and care for differences in productive ways.